Early Results of Salvage Radiotherapy for Prostate Carcinoma—Cerrahpaşa Experience - Yıldırım, Halil Cumhur; Barlas, Ceren; Öner Dinçbaş, Fazilet (Cerrahpaşa Medical Journal, 2022)
Objective: Salvage radiotherapy ± androgen deprivation therapy is the most preferred treatment for relapsed prostate cancer. The oncological outcomes of these patients vary according to pathologic and disease characteristics. We aimed to evaluate the factors affecting the oncological outcomes of patients who received salvage radiotherapy. Methods: Eighty-four patients who received salvage radiotherapy ± androgen deprivation therapy between 2003 and 2020 were reviewed. Salvage radiotherapy was administered to the prostate bed with a median dose of 66 (60-76) Gy. Pelvic lymphatic irradiation was added to 15 (18%) patients with a dose of 45-54 Gy. Half of the patients received androgen deprivation therapy. No acute grade 3-4 genitourinary and gastrointestinal side effects were observed. Late grade 3 gastrointestinal toxicity was observed in 1 patient. Kaplan–Meier test was used for survival analysis. Results: The median age was 64 (48-77) years, and the median follow-up was 42 (6-168) months. After salvage radiotherapy, 32 (38%) patients had a biochemical recurrence. The 2-year and 5-year biochemical recurrence-free survival were 82% and 55.6%, respectively. Patients who had seminal vesicle involvement (P < .001), positive pelvic lymph node (P = .002), and relapse less than 1 year (P = .002) had lower biochemical recurrence-free survival rates than others. In the multivariate analysis, recurrence within a year after surgery (P = .047; CI, 2.3 (1.0-5.1)) and seminal vesicle involvement (P = .001; CI, 4.9 (2.0-12.5)) were found to be negative factors for biochemical recurrence-free survival. Conclusion: Salvage radiotherapy achieved disease control at 5 years in half of the patients with recurrent prostate cancer. Patients with seminal vesicle involvement and early prostate-specific antigen increase after prostatectomy are at high risk of disease relapse after salvage radiotherapy. Cite this article as: Yıldırım HC, Barlas C, Dinçbaş FÖ. Early results of salvage radiotherapy for prostate carcinoma—cerrahpaşa experience. Cerrahpaşa Med J. 2023;47(1):23-27.